Phylogenetic relationships of Simpsonichthys subgenera (Cyprinodontiformes, Rivulidae), including a proposal for a new genus - Ponzetto, Josi M. [UNESP]; Britzke, Ricardo [UNESP]; Nielsen, Dalton T. B.; Parise-Maltempi, Patricia P. [UNESP]; Alves, Anderson L. [UNESP] (Wiley-Blackwell, 2016)
The systematic knowledge of Simpsonichthys has changed substantially in recent years, with five subgenera having been elevated to the genus category. In view of these taxonomic changes, the aim of the present study was to identify the phylogenetic relationships among this group in order to test a hypothesis of the division of Simpsonichthys. The ATPase 8 and 6 gene sequences of 53 specimens of Simpsonichthys, Xenurolebias, Ophthalmolebias, Spectrolebias and Hypsolebias genera were assessed. The final topology divided the Simpsonichthys subgenera into five clades: clade I (Hypsolebias antenori group and Ophtalmolebias), clade II (Simpsonichtys and Spectrolebias), clade III (Hypsolebias flammeus and H. magnificus groups), clade IV (H. notatus group) and clade V, which included the Xenurolebias genus as a sister group to all the other Simpsonichthys subgenera. Simpsonichthys, Spectrolebias and Hypsolebias could therefor not be described as monophyletic groups, as has been proposed in some hypotheses. The H. antenori, H. notatus and H. magnificus groups, however, were monophyletic. The molecular results also suggested that H. ocellatus belongs to the Hypsolebias flammeus group. The phylogenetic position of H. fasciatus suggested a new group within Hypsolebias, or possibly even a new genus. The characteristics of the Hypsolebias antenori group and their phylogenetic position suggested that only the species of this group should be included in the Hypsolebias genus. The basal position of the Hypsolebias notatus group and its morphological character may represent a new genus. Although the monophyletism of Simpsonichtys could not be recovered, the branches supported the division of the western and eastern clades, possibly due to allopatric speciation. These facts suggest the division of the genus into at least two major clades. In addition, the study of morphological and molecular data is suggested to obtain a better understanding of such complex organisms, and a major taxonomic review is required.